Mathematical games as tool for Mathematics teaching in the foundation phase - Machaba, Maphetla M (Penerbit Universiti Kebangsaan Malaysia, 2019)
Mathematics performance is a universal outcry. Children as early as foundation phase are unable to solve mathematical barriers. In her analysis Naledi Pandor, Minister of Education in South Africa noted in that only 35% of children in South Africa can read, write and count. The aim of this paper is to explore the importance of the use of educational games in teaching mathematics in the Foundation Phase (Grade zero to three) classes in South African primary schools. This research is qualitative in nature and explores the views of Foundation Phase teachers regarding the using of mathematical games as tool for mathematics teaching in the foundation phase. The concern is if the problems are not addressed in the Foundation Phase it might be too late to deal with them in the higher school grades. In fact it is known that the performance in mathematics at Grade 12 is poor as seen from the TIMMS results. The research specifically reveals that the significance of teaching children through the use mathematical games is to help inculcate strong number-sense competencies for the love of mathematics. The paper highlights the use of mathematical games for motivating and improving children’s performance and takes into account the assistance teachers should give in order to improve mathematical thinking when playing mathematical games. This paper concludes that mathematical games assist children to practise mental calculations and addresses mathematical language barriers. Teachers should teach the children to ensure that they enjoy and actively participate in the use of games when learning mathematics.